A Multifunctional Composite Hydrogel That Rescues the ROS Microenvironment and Guides the Immune Response for Repair of Osteoporotic Bone Defects. (16th March 2022) - Chen, Qixin; Li, Jiaying; Han, Feng; Meng, Qingchen; Wang, Huan; Wei, Qiang; Li, Zexi; Li, Feifei; Xie, En; Qin, Xiaoyan; Chen, Song; Wang, Weishan; et al.
Abstract: Bone repair in patients with osteoporosis remains a big challenge because their injury sites are often accompanied by an abnormal level of inflammation and reactive oxygen species (ROS). ROS is previously visualized, represented by hydrogen peroxide (H2 O2 ), in the bone defects. In this study, the H2 O2 in osteoporosis animals is further visualized, and it is found that the expression of H2 O2 is markedly higher than that in normal animals. Subsequently, a composite hydrogel containing manganese dioxide (MnO2 )‐coated calcium phosphate microspheres loaded with fibroblast activating protein inhibitor (FAPi) is prepared. Among them, MnO2 is designed to act as an advanced army to eliminate H2 O2 and generate oxygen, and constant release of FAPi is used to regulate the immune response and bone formation. In vitro experiments show that the hydrogels effectively reduce intracellular ROS, guide macrophages toward M2 polarization, and alleviate inflammation. Furthermore, the hydrogels enhance the osteogenesis and inhibit osteoclastogenesis. Animal experiments demonstrate that the hydrogels can eliminate ROS, regulate macrophages, and promote repair of osteoporotic bone defects. Together, the findings from this study imply that the multi‐pronged approach holds great promise to promote the repair of osteoporotic bone defects by rescuing the ROS microenvironment and guiding the immune response. Abstract : The composite hydrogel containing manganese dioxide (MnO2 )‐coated calcium phosphate (CaP) microspheres loading fibroblast activating protein inhibitors (FAPi) is prepared. MnO2 on the surface of microsphere can eliminate reactive oxygen species and accordingly generate oxygen in the microenvironment. The microspheres in the hydrogels slowly degrade and constantly release FAPi to inhibit FAP, which could regulate immune response and bone formation.